Woody Biomass Processing and Rural Regional Development. Issue 3 (August 2019) - Jackson, Randall W.; Borges Ferreira Neto, Amir; Erfanian, Elham; Járosi, Péter
The authors report on the economic impacts of introducing woody biomass processing in an economically distressed, but heavily forested Central Appalachian U.S. region. Woody biomass is a readily available unconventional energy source that has the potential to boost the rural region's economy. They use a static regional computable general equilibrium model to assess long-run economic impacts of two woody biomass processing production pathways of biomass to ethanol through fermentation and biomass to biofuel through fast pyrolysis. While the 232 to 370 jobs and $13 million to $21 million income might seem small relative to the multicounty region, the localized impact on the county in which the facility would be sited, even for the direct jobs and income impacts, would be much more substantial. The authors conclude that woody biomass processing is a viable economic development option for the study area and similar rural regions.